Deazaflavin Inhibitors of TDP2 with Cellular Activity Can Affect Etoposide Influx and/or Efflux - Komulainen, Emilia; Pennicott, Lewis; Le Grand, Darren; Caldecott, Keith W (ACS chemical biology, 2019)
Tyrosyl DNA phosphodiesterase 2 (TDP2) facilitates the repair of topoisomerase II (TOP2)-linked DNA double-strand breaks and, as a consequence, is required for cellular resistance to TOP2 "poisons". Recently, a deazaflavin series of compounds were identified as potent inhibitors of TDP2, in vitro. Here, however, we show that while some deazaflavins can induce cellular sensitivity to the TOP2 poison etoposide, they do so independently of TDP2 status. Consistent with this, both the cellular level of etoposide-induced TOP2 cleavage complexes and the intracellular concentration of etoposide was increased by incubation with deazaflavin, suggesting an impact of these compounds on etoposide uptake/efflux. In addition, deazaflavin failed to increase the level of TOP2 cleavage complexes or sensitivity induced by m-AMSA, which is a different class of TOP2 poison to which TDP2-defective cells are also sensitive. In conclusion, while deazaflavins are potent inhibitors of TDP2 in vitro, their limited cell permeability and likely interference with etoposide influx/efflux limits their utility in cells.
Keywords: Cell Line; biologický transport; DNA-Binding Proteins; Flavins; Biological Transport; inhibitory topoisomerasy II; kur domácí; aza sloučeniny; knihovny malých molekul; Small Molecule Libraries; Chickens; zvířata; Humans; fosfodiesterasy; Etoposide; Aza Compounds; flaviny; etoposid; Phosphoric Diester Hydrolases; Topoisomerase II Inhibitors; DNA vazebné proteiny; buněčné linie; lidé; Animals